Tippling Ladies and the Making of Consumer Culture: Gender and Public Space in Fin-de-Siècle Chicago - Remus, Emily A. (Journal of American History, 2014)
On the second day of September 1907, Reverend Frederick E. Hopkins nailed a large placard to a tree standing just beyond the doors of his church, the affluent Pilgrim Congregational Church on Chicago's South Side. The placard announced the pastor's upcoming sermon “The Growing Habit of Women Drinking Booze in Public.” No latter-day Martin Luther posting revolutionary theological doctrine on his church doors, Hopkins instead summoned congregants to protest the public consumption of alcohol by monied women in the dining establishments located within the city's new department stores, skyscrapers, and grand hotels. That Sunday the pews of the Pilgrim Church were overflowing as Hopkins declared, “When I see the girls and women of our city, as no one can help but see, going into restaurants and cafés where booze is freely served and sitting at the tables ordering and drinking cocktails and highballs with the same ease and nonchalance of manner with which they would order a cup of tea, I wonder what the society of our time is coming to and what kind of a nation we are going to become.” The sermon initiated Hopkins's month-long crusade against ladies' drinking that culminated with the pastor raiding seventeen of Chicago's “first-class” restaurants in search of women tipplers. His sensational tactics drew national press attention, yet he was hardly unique among Chicago reformers in claiming that monied women were learning to become “drunkards and moral outcasts” in fashionable new commercial public spaces.1
Keywords: Business History and gender